Spatial location of neutralizing and non-neutralizing B cell epitopes on domain 1 of ricin toxin's binding subunit. - Yinghui Rong; Greta Van Slyke; David J Vance; Jennifer Westfall; Dylan Ehrbar; Nicholas J Mantis (PLoS ONE, 2017)
Ricin toxin's binding subunit (RTB) is a galactose-/N-acetylgalactosamine (Gal/GalNac)-specific lectin that mediates uptake and intracellular trafficking of ricin within mammalian cells. Structurally, RTB consists of two globular domains, each divided into three homologous sub-domains (α, β, γ). In this report, we describe five new murine IgG monoclonal antibodies (mAbs) against RTB: MH3, 8A1, 8B3, LF1, and LC5. The mAbs have similar binding affinities (KD) for ricin holotoxin, but displayed a wide range of in vitro toxin-neutralizing activities. Competition ELISAs indicate that the two most potent toxin-neutralizing mAbs (MH3, 8A1), as well as one of the moderate toxin-neutralizing mAbs (LF1), recognize distinct epitopes near the low affinity Gal recognition domain in RTB subdomain 1α. Evaluated in a mouse model of systemic ricin challenge, all five mAbs afforded some benefit against intoxication, but only MH3 was protective. However, neither MH3 nor 24B11, another well-characterized mAb against RTB subdomain 1α, could passively protect mice against a mucosal (intranasal) ricin challenge. This is in contrast to SylH3, a previously characterized mAb directed against an epitope near RTB's high affinity Gal/GalNac recognition element in sub-domain 2γ, which protected animals against systemic and mucosal ricin exposure. SylH3 was significantly more effective than MH3 and 24B11 at blocking ricin attachment to host cell receptors, suggesting that mucosal immunity to ricin is best imparted by antibodies that target RTB's high affinity Gal/GalNac recognition element in subdomain 2γ, not the low affinity Gal recognition domain in subdomain 1α.